Frequency of Antenatal Depression Among Women with Gestational Diabetes Mellitus - Khialani, Meena Deep; Sheikh, Erum Majid; Abdul Sattar, Ayesha; Sheeri; Kashaf, Memoona; Deepa Bai (Indus Journal of Bioscience Research, 2025)
Objectives: To determine frequency of antenatal depression among pregnant women with gestational diabetes mellitus (GDM). Study Design: Descriptive, cross-sectional study. Settings: Department of Obstetrics and Gynaecology, JPMC, Karachi. Duration of study: May 2024 to October 2024. Methodology: A total of 88 women in the 16–45 age range who had gestational diabetes mellitus were included. Women who had a history of neurological diseases, chronic liver illness, pre-existing diabetes, pre-eclampsia or eclampsia, or grand-multipara (more than five births beyond viability) were not included. Age (in years), week of gestation (as determined by a consultant obstetrician using a dating scan), BMI [as defined by the operational definition] in kg/m2, gravida, para, family history of depression, place of residence (rural or urban), and booking status (booked or unbooked) were among the baseline characteristics that were recorded. Following that, a consultant psychiatrist used the 10-item MADRS score to evaluate each patient for the existence of prenatal depression. The scale’s overall score was between 0 and 60 points. If a patient’s score was greater than 12, they were diagnosed with depression. Results: The study’s participants ranged in age from 16 to 45 years, with a mean age of 29.86 ± 5.66 years. The average gestational age was 28.96 ± 4.40 weeks. The average parity was 2.83 ± 1.10. The average BMI was 29.08 ± 3.14 kg/m2. Mean MADRS score was 16.43 ± 6.75 and 25 (28.41%) of patients with GDM have antenatal depression with 52.0% have mild, 28.0% moderate and 20% having severe depression. Conclusion: This study concludes by emphasizing how physical and mental health are interwoven throughout pregnancy. In addition to being a metabolic disorder, gestational diabetes can make pregnant mothers more emotionally vulnerable.